Factores socioculturales relacionados al autocuidado del paciente del programa de Diabetes Mellitus Tipo 2, Distrito de Guadalupe. - Arce Lozano, Ana Consuelo (2022)
The purpose of this research, "Sociocultural Factors Related to Patient Self-Care of the Type 2 DM Program, District of Guadalupe", was to determine the Sociocultural Factors and their relationship with the self-care of the Type 2 DM Patient. It is descriptive, quantitative correlational. The sample was 56 patients. To identify the factors related to self-care of type 2 diabetes mellitus, a survey entitled Sociocultural Factors Related to Patient Self-Care of the Type 2 DM Program, District of Guadalupe, was applied; the results were processed in the SPSS statistical software 26. The results showed that a statistically significant relationship was found between sociocultural factors and self-care in marital status (p = 0.039) and family support (p = 0.017). However, it was not statistically significant in education level (p = 0.093), occupation (p = 0.395) and family income (p = 0.227).